SME FINANCING OF COMMERCIAL BANKS IN BANGLADESH: POLICY DIRECTIONS BASED ON SME LOAN BORROWERS’ VIEW - Rahid, Abu Obida (International Journal of Small and Medium Enterprises, 2023)
The importance of bank financing for the growth and development of Small and Medium Enterprises is extensively documented in the literature. SME finance is essential not only to starting an SME business but also to enhance the growth of the business. Unfortunately, SME businessmen are facing difficulties in getting and repaying all kinds of financing in Bangladesh. Moreover, because of financing problems, SMEs cannot enter the manufacturing industry spite many potentialities.  This research aims to identify key financing obstacles encountered by Bangladeshi SMEs and recommend policy guidelines to tackle those obstacles. Necessary data were collected through a structured questionnaire from 200 SME loan borrowers of 10 commercial banks by using a simple random sampling technique. Descriptive analysis was performed to analyze collected data. The findings indicate some constraints related to SME financing, such as higher interest rates, complex documentation, etc. SME borrowers face various obstacles before and after the sanction of SME loans. Although some initiatives related to SME financing have been adopted recently, most are not yet implemented. Moreover, SMEs' existing financing policies are inadequate, poorly designed, and inconsistent.  JEL Classification Codes: A19, B10, B25, C10, C53.